2011
DOI: 10.1038/ejcn.2011.184
|View full text |Cite
|
Sign up to set email alerts
|

Fibre intake in relation to serum total cholesterol levels and CHD risk: a comparison of dietary assessment methods

Abstract: Background/Objectives: Prospective diet diaries may be more accurate than retrospective food frequency questionnaires (FFQ). The objective of this study was to compare FFQ and 7-day diet diary (7DD) measurements of fibre intake with the incidence of coronary heart disease (CHD). Subjects/Methods: We compared 7DD and FFQ fibre intake in a nested case-control study in a population of 25 639 men and women aged 40-79 years, surveyed in 1993-97 and followed up until 2007. Among 2151 CHD cases and 5354 controls, FFQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…However, one study focusing on just the UK data from the pooled EPIC study found that fibre assessed using food diaries was protectively associated with risk, but this was not the case for fibre calculated from FFQs [40], mirroring our results. In this UK EPIC study, there was also no evidence of an association between cereal, fruit or vegetable fibre but intakes here had been assessed with weighed food diaries [40].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, one study focusing on just the UK data from the pooled EPIC study found that fibre assessed using food diaries was protectively associated with risk, but this was not the case for fibre calculated from FFQs [40], mirroring our results. In this UK EPIC study, there was also no evidence of an association between cereal, fruit or vegetable fibre but intakes here had been assessed with weighed food diaries [40].…”
Section: Discussionsupporting
confidence: 70%
“…Average NSP intake in the UKWCS, assessed by FFQ, was around 24g/day, much higher than the 18g/day NSP intake found in another UK cohort, where diet was also assessed by FFQ [40]. A Finnish study of male smokers reported mean NSP intake closer to the UKWCS intake, at around 25g/day [41].…”
Section: Discussionmentioning
confidence: 97%
“…Dietary fiber (DF) intake provides many health benefits, including benignantly changes of intestinal microflora (Tamura et al, 2011) and reductions in blood cholesterol levels (Ward et al, 2012). DF fermented in the cecum and colon by commensal microflora may improve gut health (Montagne et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, nut and cereal milks are considered as good substrates for the growth of different strains, owing to the presence of non-digestible components with prebiotic properties in both vegetable matrices. Thus, starch and fiber materials are reported to enhance the physical stability of the fermented vegetable milk and to promote the survival of the starters used, not only due to their nutritional contribution but also, since fibers are resistant to gastric juices, they act as protective barriers within the human gastrointestinal tract, (Bosnea et al, 2009;Patel, Pandiella, Wang, & Webb, 2004;Perrin, Grill, & Schneider, 2000;Wang, Conway, Brown, & Evans, 1999). Nevertheless, the ability of the starter microorganism to grow in these vegetable raw materials varies largely with the strain.…”
Section: Fermentation Of Vegetable Milksmentioning
confidence: 99%
“…Nuts are rich in mono-(MUFA) and polyunsaturated fatty acids (PUFA), vegetable proteins, dietary fiber, phytosterols, polyphenols, vitamins and minerals (Phillips, Ruggio, & Ashraf-Khorassani, 2005;Segura, Javierre, Lizarraga, & Ros, 2006). Most of those compounds have antioxidant properties and are proven to provide a beneficial effect on plasma lipid profile, low-density lipoprotein (LDL) oxidation and inflammatory processes, among others (Carlson, Eisenmann, Norman, Ortiz, & Young, 2011;Egert, Kratz, Kannenberg, Fobker, & Wahrburg, 2011;Gillingham, Harris-Janz, & Jones, 2011;Jones et al, 2011;Liu, 2012;Myers & Allen, 2012;H. A.…”
Section: Nuts and Nut Milksmentioning
confidence: 99%